Primitive Magmas in the Early Central American Volcanic Arc System Generated by Plume-Induced Subduction Initiation - Whattam, Scott A. (Frontiers in Earth Science, 2018)
Primitive magmatic rocks with Mg# ≥60 have been identified in the literature from the Sona-Azuero, Golfito and Chagres-Bayano forearc segments of southern Costa Rica and Panama of the early (75–39 Ma) Central American Volcanic Arc system (CAVAS). Primitive CAVAS basalts are remarkably similar in terms of major and many trace elements to primitive MORB and primitive basalts of the Mariana Arc and share affinities with global intra-oceanic arc tholeiitic and calc-alkaline basalts. Significant differences however, are apparent between primitive lavas of Chagres-Bayano relative to those of Sona-Azuero and Golfito. Primitive Chagres-Bayano lavas record much higher degrees of partial melting and higher amounts of shallow and deep subduction additions (e.g., higher Ba/Th, Th/Nb) than those of the older Sona-Azuero and Golfito arc segments which reflects the early petrologic and tectonic evolution of the CAVAS which is similar to other forearc systems. As shown in previous studies, early CAVAS lavas are exceptionally similar in radiogenic isotopic composition to those of the Caribbean Large Igneous Province (CLIP) oceanic plateau at 90 Ma, the approximate timing of onset of the volumetrically dominant phase of CLIP magmatism. Moreover, calculated potential temperatures of 1,633 ± 47°C for two Sona-Azuero primitive basalts suggests an anomalously hot mantle source at subduction initiation (SI). These insights are consistent with SI models which require a plume-induced SI scenario and an elevated sub-arc thermal anomaly upon inception of the CAVAS. It is postulated that, in addition to providing an anomalously high temperature regime in the sub-arc mantle at inception of the CAVAS, extrusion of the CLIP also resulted in lithospheric weakening and extension which allowed for production and rapid ascent of a high percentage of primitive magmas.